Budget allocation, maize yield performance, and food security outcomes under Malawi’s farm input subsidy programme - Mazunda, John (International Food Policy Research Institute, 2013)
Food security in Malawi is generally equated with adequate maize production as the country’s main staple crop accounts for more than 60 percent of total food consumption. Malawi has a long history of subsidizing agricultural inputs, either as a general policy to ensure national-level food security or as a response to poor harvests. As such, agricultural input subsidies targeted specifically at maize production for food self-sufficiency are a key element in the Agricultural Sector Wide Approach (ASWAp), the agricultural development framework for the government of Malawi. Since 2005, the government has implemented the Farm Input Subsidy Programme (FISP), which has been widely credited for bringing about macro-level food security in Malawi. In recent years, however, the program has come under scrutiny amid concerns about its financial sustainability and continued food security concerns at local level. This article explores the budget allocation, maize yield response, and food security outcomes of the FISP over its implementation period.